Standardisation and variation in Latin orthography and morphology (100 BC - AD 100) - Nikitina, V (2015)
The period 100 BC – AD 100 is often seen by scholars as the time when the 'standard' form of educated Latin was established. Standardisation, according to some, was the defining process for the fixing of written language and written norms. Once established, these written norms, we are led to believe, remained unchanged for the rest of the Antiquity. This study addresses this alleged standardisation of Latin in 100 BC – AD 100 by studying variations in spelling and morphology. Elimination of variation is a central part of establishing a standard language, while continuing variation characterises lack of standardisation. By studying variation in a diachronic perspective, therefore, we are able to assess the evidence for standardisation or lack thereof. Complete standardisation can be achieved mainly in spelling: therefore, the study of spelling is central for determining the existence of any standardisation movement. The first part of the thesis is dedicated to studying spelling variation in high-register formal inscriptions, where standardisation ought to be most evident. We discuss variation of the type maximus/maxumus, variant spellings ei and i for /ī/ and variation between assimilated and non-assimilated spelling of prefixes. A separate chapter addresses the spelling reform of Claudius. The second part of the thesis focuses on cases of morphological variation in literary and non-literary texts (variation between quis and quibus in the dat./abl. pl. and variation between active and deponent forms of verbs). The study of these cases of variation should add to our knowledge of language development in this period and provide a basis on which to begin a reassessment of standardisation in Latin. Language attitudes of literary authors and authors of nonliterary texts, which are relevant for the question of standardisation, will also be considered. My overall conclusion is that it is easy to exaggerate the importance of any standardising, and that it is important not to mix up uncontrolled linguistic change, which is a phenomenon of any language, and change, or fixing, that is the result of the conscious and deliberate efforts of language purists.